TINJAUAN HUKUM PROGRESIF TERHADAP WASIAT WAJIBAH BAGI KERABAT NON MUSLIM - MUHAMMAD RIDWAN (IAIN BONE, 2023)
AbstractThis study aims to describe the urgency of the position of the obligatory will for non-Muslim relatives, especially for heirs who are prevented from receiving an inheritance due to different religions from the heir. This research uses a qualitative approach, which is normative, which comes from secondary data, such as legislation, jurisprudence, and various literature related to obligatory wills for non-Muslim relatives. The results of this study indicate that the panel of judges at the Supreme Court judged that non-Muslim relatives should be eligible to receive a share of the heir's property through a will, as much as ¼ or 25%. The reason is due to consideration of the physical and emotional closeness between the heir and the heir who is hindered. Therefore, the practice of granting a mandatory will is a form of substantive justice for non-Muslim relatives, which is a progressive legal protection of their rights as heir relatives.